A comprehensive neutrosophic model for evaluating the efficiency of airlines based on SBM model of network DEA - Rasinojehdehi, Reza; Bagherzadeh Valami, Hadi (Decision Making: Applications in Management and Engineering, 2023)
This research aims to provide an innovative framework for evaluating airline performance through the networking of decision-making units (DMUs) and neutrosophic data. As a consequence, we propose a comprehensive methodology for assessing the efficiency of these decision-making units. Network data envelopment analysis (DEA) models deal with measurements of relative efficiency of DMUs when the insight of their internal structures is available. In network models, sub-processes are connected by links or intermediate products. Links have the dual role of output from one division or sub-process and input to another one. Therefore, improving the efficiency score of one division by increasing its output may reduce the score of another division because of increasing its input. To address this conflict, we proposed a new approach in Slack-Based Measure (SBM) framework and neutrosophic logic, which provide deeper insights regarding the sources of inefficiency. Our approach is a new network model, in which the intermediate products are classified into two groups of “input-type”, and “output-type” that their excesses and shortfalls directly concern with the objective function. The results of the illustrated case and analysis show that the constructed model may successfully produce performance assessments. By taking into account the number of slacks or surpluses of these products in the objective function, the proposed model gives analysts and managers a more accurate assessment of network structure efficiency. In this paper, we present a new model in the field of network data envelopment analysis with SBM approach in a neutrosphonic environment, in which for the first time the nature of intermediate products in terms of input or output is investigated. Also, the proposed framework is the first attempt to performance evaluation in neutrosophic network DEA.